ICTs Supported Agricultural Extension Services: A Study on Information Access for Farmers in Barnala District of Punjab - Singh, Suryendra; P. S. Tanwar; Sharma, Anjuly (Journal of Agricultural Extension Management, 2021)
ICTs have enormous potential to improve e-extension advisory services if taken advantage of by the 'extension agents' in the diffusion process of innovations. ICTs can play a crucial role in strengthening the capacity of farmers and the field level extension functionaries and intermediaries. The purpose of the study was to analyze the use of different ICTs in agricultural knowledge pathways, the dissemination pathways, line departments, and socio-economic factors. Data were analyzed manually and using R software (version 3.6.1). A total of one hundred farmers were interviewed, with a purposively selected sample of 60 farmers, using a pre-formulated questionnaire from all three blocks of Barnala district. The findings indicate that farmers depend on four major ICT applications viz., mobile apps, television, internet browsing and Facebook to access information. The lack of harmonization and weak linkages between line departments in utilizing the existing ICT tools, level of ICT ownership and access to information at the household level were found important challenges for ICT-enabled agricultural extension services.